POTRET UKHUWAH ISLAMIYAH DALAM AL-QUR’AN: UPAYA MERAJUTNYA DALAM KEHIDUPAN UMAT ISLAM - Syeikh, Abdul Karim (Forum Intelektual Qur'an dan Hadits Asia Tenggara (SEARFIQH) Kota Banda Aceh, 2019)
This writing aims to reveal how the portrait of Ukhuwah Islamiyah in the Qur'an? The next question is, what is the source of the fracture of Ukhuwah Islamiyah according to the Qur'an? Then, how to knit Ukhuwah Islamiyah which has been cracked so far? To get answers to the questions above, researchers used a type of library research (library research) and classified as qualitative research. The research method used is the maudhu'iy (thematic) method which is presented descriptively-qualitatively. After conducting the research, it was obtained that the equality of faith and religion became the main portrait of the bonding of Ukhuwah Islamiyah among Muslims. The Qur'an as a guide to the lives of Muslims which contains the teachings and provisions of the laws of Allah becomes the bonding heart of every Muslim and Muslim to obey Allah who has set up fellow believers so that they are kept from slipping into lust and protected from temptation shaytan. According to the Qur'an, the source of the fracture of the Ukhuwah Islamiyah was due to the shallowness of the mastery of Islamic religious knowledge so that they were dragged into an understanding of Islam in a narrow and partial way. Another source of cracking in Ukhuwah Islamiyah is due to the development of envy and jealousy among groups of Islamic society. Attitude to prioritize emotions and deny the use of common sense in resolving differences of opinion in worship practices carried out by Muslim communities also triggers the destruction of Ukhuwah Islamiyah. The next source of fracture is due to the uncontrolled development of power, position, material, wealth and popularity among some Muslims. The cracks of Ukhuwah Islamiyah can be knitted back by restoring the commitment of every Muslim and Muslim person to uphold the Qur'an and the sunnah of the Prophet Muhammad SAW, by developing enthusiasm and mutual cooperation and supporting each other on the provisions of religious teachings that are ushuliyah (the main points the teachings of Islam) and mutual attitude tasamuh (tolerance) to the teachings of Islam that is furu'iyah which is permitted by Shari'at disagree. The use of the principle of tarjih in the process of thinking and the use of the principle of maintaining silaturrahim relations in charity and trying to discard the attitude of suuzhzhan (prejudiced) to other parties with different opinions from groups or groups and develop the attitude of husnuzhzhan (good prejudice) to fellow Muslims even though they are different from the group.